Speciation of Cr(III) and Cr(VI) in surface waters with a Chelex-100 resin column and their quantitative determination using inductively coupled plasma mass spectrometry and instrumental neutron activation analysis - Md Yusof, Aminah; Chia, C.H.; Wood, Abdul Khalik (Akademiai Kiado, 2007)
Inorganic Cr(III) and Cr(VI) have contrasting biological, geochemical and toxicology effects. Cr(III) is considered as an essential species for the proper functioning of living organisms but Cr(VI) is toxic for the biological systems. An off-line speciation method using Chelex-100 has been practiced for speciation to Cr(III) and Cr(VI) from surface waters of rivers. The underlying principal of this separation method is based on the ability of cationic Cr(III) to be retained by the resin Chelex-100 while the anionic Cr(VI) remained in the sample matrices. The efficiency of this technique was improved by studying the effect of resin pH. Quantitative determination using inductively coupled plasma-mass spectrometry (ICP-MS) and instrumental neutron activation analysis (INAA) was carried out after the separation to determine the total Cr and Cr(VI) in the liquid matrices. The precision and the accuracy of the quantitative analysis were evaluated by using standard reference material NRCC CASS-2 Intercomparison of INAA and ICP-MS results were determined. The quantity of inorganic Cr(III) and Cr(VI) in the surface water of rivers in the vicinity of industrial areas was investigated together with the determination of the physical properties of the water rivers during sampling.